Craniocervical Junction Venous Anatomy on Enhanced MR Images: The Suboccipital Cavernous Sinus - Caruso, Ronald D.; Rosenbaum, Arthur E.; Chang, Ja Kwei; Joy, Stephen E. (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: The suboccipital cavernous sinus, a vertebral venous plexus surrounding the horizontal portion of the vertebral artery at the skull base, provides an alternative pathway of cranial venous drainage by virtue of its connections to the cranial dural sinuses, the vertebral venous plexus, and the jugular venous system. Knowledge of the anatomy of this system facilitates interpretation of images and might reduce the number of false-positive diagnoses of lesions, such as adenopathy or schwannoma. We hypothesized that this circulation could be visualized on contrast-enhanced, fat-suppressed T1-weighted MR images.METHODS: The craniocervical junctions of 14 patients were scanned using fat-suppressed, contrast-enhanced, T1-weighted MR sequences and evaluated for visibility of the following venous structures: suboccipital cavernous sinus, vertebral artery venous plexus, anterior and posterior condylar veins, vertebral venous plexus, internal jugular vein, and the marginal sinus. Both the right and left sides were assessed in at least two planes. The venous diameters were also measured.RESULTS: All the evaluated venous structures were seen routinely in all three planes, with the exception of the posterior condylar vein, known to be variably present, which was seen only one third of the time in the sagittal plane and two thirds of the time in the other planes. The posterior condylar vein also showed the greatest variability in size and symmetry.CONCLUSION: The suboccipital cavernous sinus and most of its associated venous circulation at the skull base are easily identified on contrast-enhanced, fat-suppressed T1-weighted MR images. The posterior condylar vein, known to be variably present, was not well seen in the sagittal plane and displayed the greatest variability in size and symmetry.